Determination of mixing and compacting temperatures for hot mix asphalt - Ithnin, Noorafidah (2008)
Malaysia has been using bitumen grade of 80-100 penetration for many years. The typical mixing and compacting temperature has been normally set as 160°C and 140°C respectively based on experience for the lab procedure purpose. With the newly revised Specification of Roadwork 2007 by JKR, new bitumen grade had been introduced including grade 60-70 and some other types of modified bitumen. The objective of this study is to determine the appropriate mixing and compacting temperature for the bitumen grades by viscosity and correlation with other physical properties of bitumen. Rotational Brookfield Viscometer was used to determine the correct temperature for viscosity at 165°C and 135°C and at viscosity ranges of 0.17±0.02 and 0.28±0.03 Pa s for mixing and compacting, respectively as per ASTM D 2493. The result shows that the PEN 60/70 bitumen, PG 76 and PG 82 show higher mixing and compacting temperature than PEN 80/100. It also indicates that penetration shows close relationship with viscosity and could be used to determine the mixing and compacting temperatures.